Infecção chagásica em candidatos a doação de sangue e de órgãos no estado do Ceará - Costa, Alanna Carla (2017)
Introduction: Chagas’ disease still represents a serious public health problem in Latin America, despite all steps of control. Blood transfusion and organ transplantation have acquired enormous relevance in the epidemiology of Chagas’ disease, assuming the role as the main route of transmission in places where screening for Trypanossome cruzi has not been performed yet. The main objective of this study is to know the positivity for T. cruzi in candidates for blood and organ donation in the State of Ceara. Methodology: It is a retrospective descriptive study, during the period 2010-2015, which was carried out analyzing medical records from Transplantation Central of the State of Ceara and data recorded in the computerized system from the Hematology and Hemotherapy Center of the State of Ceara (HEMOCE). For the association of categorical variables and groups, the Fisher’s exact test was used. For establishing a linear relationship among quantitative variables, it has been used the simple linear regression. The project was approved by Research Ethical Committee of the Federal Univesity of Ceara. Results: Concerning potential organ donors, 2,822 potential donors were notified; 1,038 of them were effective donors and 1,784 were excluded for several reasons. The prevalence of T. cruzi infection in potential donors was 1.27% (n.29). From the reactive cases, 79.31%(23) were male aged 41 to 60 years, most them coming from countryside cities of the state (65.5%, n:19). 72.4% (21) presented reactive serology for other infections besides CD, such as Cytomegalovirus, Hepatitis B and C and Toxoplasmosis. It was observed that, among potential organ donors with CD, there was higher probability to find people over 60 years, having the stroke (CVA) as the main cause of death. Regarding the potential blood donors, 608,353 were serologically screened, being that 1,982 (0.3%) were serologically ineligible due to reactivity to CD. The indeterminate results for CD corresponded to 5.99% (n.1380) of the total of blood bags discarded during the period of the study. 763 individuals had previously donated blood, subsequently, they were turned away due CD discovered by serological screening tests. There were 120 ineligible individuals confirmed. From them, majority were male over 30 years old, with high school education, from countryside cities of the state and coming from the capital Fortaleza. Conclusion: Although we have observed a considerable decrease in the prevalence of the disease in blood and organ donors in the state of Ceara, CD still represents a problem in our state, therefore the vector surveillance and the hemovigilance in blood banks must be encouraged continuously to avoid outbreaks and keep the disease under control. In addition, the number of undetermined serological results draws attention, then it is necessary to promote studies which propose new methodologies for the serological tests, increasing their specificity and, consequently, reducing the rate of discard of blood bags to reduce costs for the Unified Health System.